AB0578 Tocilizumab influence on the serum lipid profiles and rapid progression of intima media-thickness in patients with rheumatoid arthritis. (23rd January 2014) - Popkova, T.; Novikova, D.; Udachkina, E.; Panasuk, E.; Avdeeva, A.; Alexandrova, E.; Novikov, A.; Volkov, A.; Nasonov, E.
Abstract : Background: Rheumatoid arthritis (RA) is characterized by a high risk of cardiovascular events (CVE) associated with atherosclerosis (AS). A key role in the development of AS belongs to rheumatoid inflammation. Influence of biologic therapy on the cardiovascular system is not enough studied. Objectives: to assess the of tocilizumab (TCZ) therapy on lipid profile and carotid intima-media thickness (cIMT) in RA patients (pts). Methods: 43 RA pts with moderate/good effect (EULAR) of TCZ therapy, mean age 51 (43;55) years, disease duration - 56 (23;81) months were included in the study. Cardiovascular disease has 26/43 RA pts: arterial hypertension - 23 (52%), ischemic heart disease – 5 (12%) pts. All pts received TCZ 8 mg/kg intravenously every four week. Serum total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low- density lipoprotein cholesterol (LDL-C), the atherogenic index (AI): TC-HDL-C/HDL-C as well as disease activity score (DAS28), C-reactive protein (CRP), IgM RF, HAQ, cIMT were examined at baseline and after 24 weeks of TCZ treatment. Abnormal lipid levels were defined according to the European Society of Cardiology (ESC) guidelines as TC≥5, 0mmol/l, LDL-C≥3, 0 mmol/l, TG≥1, 7mmol/l, HDL-C≤1, 4mmol/l. The cIMT was evaluated by high resolution B-mode ultrasound. Results: The dynamic of TC, LDL-C, HDL-C, TG levels on baseline and after 24 weeks TCZ treatment were 5.0 and 5.9mmol/l (Δ+11, 6%); 3, 4 and 3, 1 mmol/l (Δ-1, 6%) (p>0, 05); 1, 2 and 2, 1 mmol/l (Δ+48, 9%); 1, 2 and 1, 1 mmol/l (Δ-7, 0%) accordingly; the AI was 3, 2 at baseline and decreased to 2, 0 (Δ-31, 9%) (p<0, 05). The dynamic of abnormal lipid levels on baseline and after 24 weeks TCZ treatment were for TC≥5, 0mmol/l (48% and 67%, ), LDL-C≥3, 0 mmol/l (58% and 56%), TG≥1, 7mmol/l (16% and 21%) (ND), HDL-C≤1, 4mmol/l (65% and 19%) (p<0, 05). The percentages AI>3, 0 was 44% RA pts at baseline and after 24 weeks TCZ treatment decreased to 9% pts. The cIMT was 0.84 mm at baseline and increased to 0.94 mm (Δ+8, 2%) (p=0.001). cIMT positively correlated with age (r=0, 77), levels of TC (r=0, 33), TG (r=0, 38), LDL-C (r=0, 35) at baseline and after 24 weeks of TCZ treatment (p<0, 05). cIMT did not correlate with AI after six months observation. Plaques were detected in 17/41 (41, 4%) RA pts before treatment TCZ and after 24 weeks TCZ treatment amount of AC increased to 53, 6% RA pts. The lipid profile changes associated with a significant decrease in CRP level (from 33, 5 and 0, 64 mg/l (Δ-97, 4%)); DAS 28 (from 6, 5 and 2, 1 (Δ-66, 6%)); IgM RF (from 255 and 90, 7 mg/l (Δ-42, 4%)) and HAQ (from 1, 75 and 0, 56 (Δ-65, 5%)), p<0, 05. During the treatment serious deterioration in health such as cardiovascular events were not observed, however, we observed destabilization of arterial hypertension in four RA pts. Three RA pts with coronary heart disease had a new episode of silent ischemia. That requires prescription of antihypertensive and antiischemic drugs at higher doses. Conclusions: TCZ-induced changes in lipid levels and cIMT are associated with suppression of systemic inflammation. TCZ therapy leads to an increase of antiatherogenic lipoprotein level (HDL-C) and decrease of AI, as well as cIMT thickening. Cardiovascular effects of TCZ remains for future investigations. Disclosure of Interest: None Declared